On the Expressive Completeness of Underspecified Representations - Ebert, Christian (Proceedings of the Amsterdam Colloquium, 2003)
One property of underspecified representation formalisms is that of expressive completeness, i.e. the ability to provide representations for all possibly occuring sets of readings. In this paper a general and formal definition of completeness along the lines of [6] will be given. Several formalisms will then be compared concerning their expressive power and shown to be incomplete.